Centimeter-level coal gangue aggregate roadway shotcrete material and preparation method thereof
Patent Information
- Application Number
- CN202611020426.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-09-18
AI Technical Summary
[0011]本发明针对现有喷浆材料中厘米级煤矸石骨料利用率低、煤矸石堆积造成环境污染、传统喷浆材料成本高以及现有固废利用技术中煤矸石掺量低等技术问题,提供一种厘米级煤矸石骨料巷道喷浆材料及其制备方法
[0048] 1. This invention achieves high-volume utilization of centimeter-sized coal gangue aggregate. Through a four-stage aggregate gradation reconstruction technology, coal gangue particles with a particle size range of 0-1 cm are gradient-filled according to a specific ratio (0-0.3 cm: 0.3-0.6 cm: 0.6-0.8 cm: 0.8-1 cm = 25%-30%: 25%-30%: 20%-25%: 20%-25%). This allows aggregate particles of different sizes to fill and densely pack each other, forming a compact skeleton structure, reducing the porosity of the shotcrete layer to below 18%. As a result, the content of coal gangue aggregate in the shotcrete material can reach 60%-70%, far exceeding the traditional technology's level of less than 20% for centimeter-sized coal gangue aggregate. This technological breakthrough enables the direct resource utilization of large amounts of coal gangue solid waste underground, effectively solving the problems of land occupation and environmental pollution caused by coal gangue accumulation.
Smart Images

Figure CN122771689A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of mine support materials technology, and in particular to a centimeter-scale coal gangue aggregate roadway shotcrete material and its preparation method. Background Technology
[0002] Shotcrete support for coal mine roadways is a crucial technical means to ensure safe underground production. After the shotcrete material is sprayed onto the surface of the surrounding rock in the roadway, it forms a support layer of a certain thickness, effectively sealing the surrounding rock, preventing weathering and spalling, and improving the load-bearing capacity of the surrounding rock. Currently, shotcrete support for coal mine roadways mainly uses cement-based shotcrete materials, with cement as the binder and natural sand and gravel as aggregate, mixed in a certain proportion and sprayed onto the roadway surface by a shotcrete machine.
[0003] However, existing shotcrete materials have the following technical problems:
[0004] First, aggregate crushing is energy-intensive. Existing shotcrete materials require aggregate particle sizes ≤5mm, and aggregates with particle sizes ≤5mm must account for more than 50% of the shotcrete material. Crushing coal gangue to below 5mm requires a large amount of electricity, resulting in high crushing costs and generating a large amount of dust during the crushing process, causing environmental pollution.
[0005] Second, the utilization rate of centimeter-sized coal gangue aggregate is low. Due to the poor interfacial bonding performance between centimeter-sized aggregate (particle size > 5mm) and cementitious materials, the content of centimeter-sized coal gangue aggregate in traditional technologies is usually less than 20%. When the content of centimeter-sized coal gangue aggregate exceeds 20%, the porosity of the shotcrete layer will exceed 25% (see "Coal Science and Technology"), seriously affecting the density and durability of the shotcrete layer. This makes it impossible to effectively utilize a large amount of coal gangue in the shotcrete material.
[0006] Third, coal gangue accumulation causes serious environmental problems. Coal gangue is the main solid waste generated during coal mining and washing. my country's cumulative coal gangue stockpile has exceeded 7 billion tons, with more than 2,600 gangue dumps. The large-scale accumulation of coal gangue not only occupies valuable land resources, but also causes heavy metal ions to leach out from the sulfides and other harmful substances in the gangue after being leached by rainwater, polluting the surrounding soil and water bodies. At the same time, coal gangue dumps pose a risk of spontaneous combustion, releasing harmful gases such as sulfur dioxide, severely polluting the atmospheric environment.
[0007] Fourth, traditional shotcrete materials are costly and resource-intensive. The aggregates for traditional shotcrete materials rely on natural sand and gravel, which are non-renewable resources; over-exploitation will damage the ecological environment. As natural sand and gravel resources become increasingly depleted, their procurement costs continue to rise, leading to a continuous increase in shotcrete support costs.
[0008] Fifth, existing solid waste utilization technologies suffer from low coal gangue content and insufficient activation of its activity. Although some technologies have attempted to use coal gangue in shotcrete materials, the coal gangue content is usually less than 30%, and the pozzolanic activity of coal gangue is not fully activated, resulting in the mechanical properties of the shotcrete materials failing to meet the requirements of underground support.
[0009] To address the aforementioned technical issues, researchers have conducted relevant explorations. For example, Chinese invention patent CN1281829A discloses a material and preparation method for jet propulsion support in underground roadways, with self-igniting ceramsite having a particle size ≤15mm and a ratio of self-igniting ceramsite to cement of 2:1 to 7:1. While this technology utilizes coal gangue, it uses self-igniting coal gangue ceramsite, requiring the coal gangue to undergo sufficient self-ignition treatment beforehand, resulting in a complex process and environmental pollution from the self-ignition process itself. Another example is Chinese invention patent CN115321888A, which discloses a coal gangue roadway spray material and its preparation method, mixing de-pulverized coal gangue, sand, slag powder, fly ash, silica fume, gypsum, etc., to prepare the spray material. However, in this technology, coal gangue still needs to be used in combination with other aggregates (such as sand), failing to reflect the dominant role of coal gangue as an aggregate, and its aggregate gradation has not been systematically optimized. For example, the multi-component solid waste spraying material technology optimizes the gradation of coal gangue aggregates with multiple particle sizes, and combines the synergistic effects of fly ash, slag and other solid wastes to construct a compact spatial packing structure. However, the particle size distribution of the coal gangue aggregates in this technology is multiple levels such as 2.36~4.75mm, 1.18~2.36mm, and 0.6~1.18mm, which still belong to the category of millimeter-level fine aggregates. It fails to solve the problem of efficient utilization of centimeter-level coal gangue aggregates, and its cementing system does not include the synergistic combination of desulfurization gypsum and silica fume.
[0010] In summary, there is currently no roadway shotcrete material that can utilize centimeter-sized (0-1cm) coal gangue as the main aggregate, achieve high admixture (60%-70%) utilization, and simultaneously ensure low resilience and high strength. Therefore, developing a roadway shotcrete material that can efficiently utilize centimeter-sized coal gangue aggregate and its preparation method has significant practical importance and broad application prospects. Summary of the Invention
[0011] This invention addresses the technical problems of low utilization rate of centimeter-sized coal gangue aggregate in existing shotcrete materials, environmental pollution caused by coal gangue accumulation, high cost of traditional shotcrete materials, and low coal gangue content in existing solid waste utilization technologies. It provides a centimeter-sized coal gangue aggregate roadway shotcrete material and its preparation method.
[0012] One objective of this invention is to provide a roadway shotcrete material with centimeter-sized coal gangue (0~1cm) as the main aggregate. Through the synergistic effect of four-grade aggregate gradation reconstruction and multi-element cementitious system, a high admixture (60%~70%) of coal gangue aggregate in the shotcrete material is achieved.
[0013] Another objective of this invention is to provide a method for preparing the above-mentioned centimeter-sized coal gangue aggregate roadway shotcrete material, which is simple in process, easy to operate, and suitable for industrial production.
[0014] The technical problems to be solved by this invention also include: how to improve the interfacial bonding performance between centimeter-sized coal gangue aggregate and cementitious materials, and reduce the porosity of the shotcrete layer; how to reduce the rebound rate during shotcrete construction and reduce material waste; and how to ensure that the shotcrete material can make the maximum use of coal gangue solid waste resources while meeting the strength requirements of underground support.
[0015] The above-mentioned objective of this invention is achieved through the following technical solutions:
[0016] A centimeter-scale coal gangue aggregate roadway shotcrete material, composed of the following raw materials by mass percentage:
[0017] Coal gangue aggregate 60%~70%;
[0018] Cementitious materials: 30%~40%;
[0019] The cementitious material contains 0.8% to 3% of a quick-setting agent, 0.1% to 0.5% of a water-reducing agent, and 2% to 5% of a water glass.
[0020] The coal gangue aggregate has a particle size of 0-1 cm, and is composed of particles of the following four particle size grades according to mass percentage:
[0021] Particles with a diameter of 0-0.3 cm account for 25%-30%;
[0022] Particles with a diameter of 0.3~0.6cm account for 25%~30%;
[0023] Particles with a diameter of 0.6~0.8cm account for 20%~25%;
[0024] Particles with a diameter of 0.8 to 1 cm account for 20% to 25%.
[0025] The cementitious material is composed of the following components by mass percentage:
[0026] Ordinary Portland cement 20%~50%;
[0027] Slag powder 40%~60%;
[0028] Desulfurized gypsum 6%~10%;
[0029] Silicon powder 5%~10%;
[0030] Fly ash 10%~20%.
[0031] Preferably, the ordinary silicate cement is grade 42.5 or grade 42.5R ordinary silicate cement.
[0032] Preferably, the slag powder is S95 or S105 grade slag powder with a specific surface area ≥450m² / kg.
[0033] Preferably, the desulfurized gypsum contains ≥90% dihydrate gypsum; the silica powder has an average particle size of 0.1~0.3μm; and the fly ash is grade II or higher fly ash.
[0034] Preferably, the accelerator is an alumina clinker-based accelerator or a liquid accelerator, with an initial setting time ≤2 min and a final setting time ≤10 min; the water-reducing agent is a polycarboxylate-based high-performance water-reducing agent with a water reduction rate ≥30%.
[0035] Preferably, the water-cement ratio of the sprayed material is 0.35 to 0.40.
[0036] A method for preparing the above-mentioned centimeter-sized coal gangue aggregate roadway shotcrete material includes the following steps:
[0037] Step S1: Crush the coal gangue raw material to a particle size ≤1cm;
[0038] Step S2: The crushed coal gangue particles are screened and graded, and collected separately according to four particle size grades: 0~0.3cm, 0.3~0.6cm, 0.6~0.8cm, and 0.8~1cm. They are then mixed evenly in proportions of 25%~30%, 25%~30%, 20%~25%, and 20%~25% by mass to obtain coal gangue aggregate.
[0039] Step S3: The coal gangue aggregate obtained in step S2 is subjected to magnetic separation to remove iron, and dust suppression spraying is carried out simultaneously during the magnetic separation process.
[0040] Step S4: Weigh out ordinary Portland cement, slag powder, desulfurized gypsum, silica fume and fly ash according to the proportion, mix them evenly to obtain cementitious material;
[0041] Step S5: Dry mix the coal gangue aggregate obtained in step S3 with the cementitious material obtained in step S4 for 3-5 minutes to obtain a dry mix.
[0042] Step S6: Dissolve the quick-setting agent, water-reducing agent and water glass in water to obtain an additive aqueous solution, and then add it to the dry mixture obtained in step S5. Control the water-cement ratio to be 0.35~0.40, stir evenly, and obtain the spray slurry.
[0043] Step S7: The slurry obtained in step S6 is pumped by a screw pump and sprayed through the spraying equipment.
[0044] Preferably, the crushing process in step S1 uses a combination of a jaw crusher and an impact crusher, and the maximum particle size of the crushed coal gangue particles does not exceed 1 cm.
[0045] Preferably, the magnetic separation for iron removal in step S3 uses a permanent magnet separator or an electromagnetic separator with a magnetic field strength ≥3000Gs; the dust suppression spraying uses an atomized spraying method with a spraying water volume of 1%~3% of the coal gangue aggregate mass.
[0046] Preferably, the spraying construction in step S7 adopts a wet spraying method or a damp spraying method; in the wet spraying method, the spraying slurry is sprayed within 30 minutes after mixing; the pumping pressure of the screw pump is 0.3~0.8MPa, the spraying distance is 0.8~1.5m, and the spraying angle is 70°~90°.
[0047] In summary, compared with the prior art, the present invention has at least one of the following beneficial technical effects:
[0048] 1. This invention achieves high-volume utilization of centimeter-sized coal gangue aggregate. Through a four-stage aggregate gradation reconstruction technology, coal gangue particles with a particle size range of 0-1 cm are gradient-filled according to a specific ratio (0-0.3 cm: 0.3-0.6 cm: 0.6-0.8 cm: 0.8-1 cm = 25%-30%: 25%-30%: 20%-25%: 20%-25%). This allows aggregate particles of different sizes to fill and densely pack each other, forming a compact skeleton structure, reducing the porosity of the shotcrete layer to below 18%. As a result, the content of coal gangue aggregate in the shotcrete material can reach 60%-70%, far exceeding the traditional technology's level of less than 20% for centimeter-sized coal gangue aggregate. This technological breakthrough enables the direct resource utilization of large amounts of coal gangue solid waste underground, effectively solving the problems of land occupation and environmental pollution caused by coal gangue accumulation.
[0049] 2. The interface-enhanced cementitious system significantly improves the interfacial bonding performance of centimeter-sized aggregates. This invention employs a multi-component cementitious system composed of ordinary silicate cement, slag powder, desulfurized gypsum, silica fume, and fly ash. Specifically, desulfurized gypsum reacts with tricalcium aluminate from cement hydration products to generate ettringite (AFt). ettringite exhibits micro-expansion, compensating for shrinkage defects at the interface of large aggregates and enhancing interfacial bonding strength. Silica fume has an average particle size of only 0.1~0.3μm, filling the micron-sized pores at the aggregate-cement interface. Simultaneously, the pozzolanic activity of silica fume reacts with calcium hydroxide produced during cement hydration to generate CSH gel, further densifying the interfacial transition zone. The ettringite (micron-sized) generated from desulfurized gypsum and the CSH gel (nano-sized) generated from silica fume together form a "dual-size gel composite network," simultaneously compensating for and strengthening interfacial defects of large aggregates at both the micron and nanoscales. This solves the technical problem of high porosity and low strength in the sprayed layer caused by poor interfacial bonding of centimeter-sized aggregates.
[0050] 3. Excellent shotcrete performance. The shotcrete material of this invention has a rebound rate of ≤10% (measured value as low as 8.7%), far lower than the industry standard requirement of ≤15%. A low rebound rate means less material waste during shotcrete construction, significantly reducing construction costs. Simultaneously, the shotcrete material of this invention has a 1-day compressive strength ≥6.5MPa (measured value 6.5MPa), a 28-day compressive strength ≥26MPa (measured value 26.3~28.99MPa), a 28-day flexural strength ≥4.5MPa (measured value 4.8~5.2MPa), and a permeability coefficient (28 days) ≤1.5×10⁻⁶. -11 m / s (measured value 0.8×10) -11 ~1.2×10 -11 (m / s), and all performance indicators meet or exceed the requirements of industry standard MT / T 5014-2010.
[0051] 4. Raw materials are widely available and inexpensive. This invention uses coal gangue as the main aggregate and industrial solid waste such as slag powder, desulfurized gypsum, and fly ash as cementing materials, making extensive use of industrial solid waste and reducing the amount of natural sand and gravel aggregate and cement. Compared with traditional shotcrete materials using natural sand and gravel as aggregate, the material cost of this invention can be reduced by more than 30%. Furthermore, the coal gangue is used directly underground, avoiding the cost of lifting and transporting it to the surface, further reducing overall costs.
[0052] 5. High construction efficiency. The spraying speed of the shotcrete material of this invention can reach 8.5 m³ / h, which is higher than the 6 m³ / h of the traditional method, and can effectively shorten the construction period of roadway shotcrete support.
[0053] 6. Green and environmentally friendly. This invention can dispose of large quantities of industrial solid waste such as coal gangue, slag, desulfurization gypsum, and fly ash, realizing the harmless and resource-based utilization of solid waste resources, which is in line with national strategies and the policy orientation of green mine construction. Attached Figure Description
[0054] Figure 1 This is a schematic diagram of the process flow for the preparation method of centimeter-sized coal gangue aggregate roadway shotcrete material according to the present invention. Detailed Implementation
[0055] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0056] Example 1
[0057] This embodiment provides a centimeter-scale coal gangue aggregate roadway shotcrete material and its preparation method.
[0058] 1. Raw material preparation
[0059] The raw materials used in this embodiment are as follows:
[0060] (1) Coal gangue aggregate: Coal gangue was taken from the coal preparation plant of a certain coal mine, crushed and screened, and then mixed according to a four-grade ratio. The specific composition of the four-grade ratio is as follows: 28% of the particles with a particle size of 0~0.3cm, 27% of the particles with a particle size of 0.3~0.6cm, 23% of the particles with a particle size of 0.6~0.8cm, and 22% of the particles with a particle size of 0.8~1cm. The mass percentage of coal gangue aggregate in the shotcrete material is 65%.
[0061] (2) Cementitious materials: Composed of the following components by mass percentage: 35% ordinary Portland cement of grade 42.5, 40% slag powder of grade S95 (specific surface area 480 m² / kg), 8% desulfurized gypsum (92% dihydrate gypsum content), 7% silica fume (average particle size 0.2 μm), and 10% secondary fly ash. The cementitious materials account for 35% of the mass percentage of the shotcrete material.
[0062] (3) Admixtures: by mass of cementitious materials: 1.5% quick-setting agent (aluminum-oxygen clinker system), 0.3% water-reducing agent (polycarboxylate system, water reduction rate 32%), and 3% water glass.
[0063] 2. Preparation method
[0064] Please see Figure 1 The preparation method of this embodiment includes the following steps:
[0065] S1: The coal gangue raw material is fed into a jaw crusher for coarse crushing, and the coarsely crushed material is then fed into an impact crusher for fine crushing until all particles have a diameter of ≤1cm.
[0066] S2: The crushed coal gangue particles are fed into a vibrating screen for screening and grading, and collected separately according to four particle size grades: 0~0.3cm, 0.3~0.6cm, 0.6~0.8cm, and 0.8~1cm. Then, the four grades of aggregate particles are mixed evenly in the following proportions by mass percentage: 0~0.3cm accounts for 28%, 0.3~0.6cm accounts for 27%, 0.6~0.8cm accounts for 23%, and 0.8~1cm accounts for 22%, to obtain coal gangue aggregate.
[0067] S3: The coal gangue aggregate obtained in step S2 is fed into a magnetic separator via a belt conveyor for magnetic separation and iron removal. The magnetic separator uses a permanent magnet separator with a magnetic field strength of 3500 Gs. During the magnetic separation process, an atomizing spray device is simultaneously activated for dust suppression, with the spray water volume being 2% of the mass of the coal gangue aggregate.
[0068] S4: Weigh out 42.5 grade ordinary Portland cement, S95 grade slag powder, desulfurized gypsum, silica fume and secondary fly ash according to the proportion, and put them into a dry powder mixer to mix evenly for 5 minutes to obtain cementitious material.
[0069] S5: The coal gangue aggregate obtained in step S3 and the cementitious material obtained in step S4 are fed into a dry powder mixer at a mass ratio of 65:35 for dry mixing. The dry mixing time is 4 minutes to obtain the dry mixture.
[0070] S6: Dissolve the accelerator, water-reducing agent, and water glass in water according to the specified ratio to obtain an admixture aqueous solution. Add the admixture aqueous solution to the dry mixture obtained in step S5, control the water-cement ratio to be 0.38, and use a forced mixer to mix evenly for 3 minutes to obtain the spray slurry.
[0071] S7: The grout obtained in step S6 is pressurized by a screw pump with a pumping pressure of 0.5 MPa and then sprayed using a spraying device. The spraying is carried out using a wet spraying method with a spraying distance of 1.2 m and a spraying angle of 80°. The spraying is completed within 25 minutes after the grout is mixed.
[0072] 3. Performance Testing
[0073] The performance of the sprayed material prepared in this embodiment was tested using the following methods:
[0074] (1) Setting time test: The test was conducted in accordance with GB / T 1346-2011 "Test methods for standard consistency water requirement, setting time and soundness of cement". The test results were: initial setting time 1.5 min, final setting time 8 min.
[0075] (2) Compressive strength test: The test was conducted according to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". The sprayed mortar was molded into specimens of 40mm×40mm×160mm and cured under standard curing conditions (temperature 20±2℃, relative humidity ≥95%) for 1d, 3d, 7d and 28d respectively before compressive strength testing. The results of the compressive strength test at each age are shown in Table 1.
[0076] Table 1 Compressive strength of shotcrete material at different ages in Example 1
[0077]
[0078] (3) Flexural strength test: The test was conducted in accordance with GB / T 17671-2021. The flexural strength of the specimens cured for 28 days was tested, and the test result was: 28-day flexural strength 5.2 MPa.
[0079] (4) Porosity test: The porosity was tested using the mercury intrusion porosimetry (MIP) method according to the "Method for Testing Porosity of Concrete". The test result was: the porosity of the shotcrete layer was 16.8%.
[0080] (5) Permeability coefficient test: The test was conducted according to GB / T50082, "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete", with a curing period of 28 days. The test result was: permeability coefficient 0.8 × 10⁻⁶. -11 m / s.
[0081] (6) Microstructure Analysis: The microstructure of the shotcrete material samples cured for 28 days was observed using scanning electron microscopy (SEM) at a magnification of 5000x. The results showed that ettringite (AFt), formed by the reaction of desulfurized gypsum and cement hydration products, was in the form of needle-like crystals, interspersed in the interface region between aggregate and cementitious material; CSH gel, formed by silica fume hydration, was in the form of flocculent or network-like structures, filling the micropores between the ettringite crystals. The ettringite (micrometer-scale) and CSH gel (nanometer-scale) together formed a "dual-size composite network structure," simultaneously strengthening the aggregate-cementant interface at both the micrometer and nanometer scales. A detailed description of this microstructure is shown in Table 2.
[0082] Table 2. Microstructural characteristics of hydration products of sprayed material in Example 1 (SEM observation)
[0083]
[0084] 7. Lane spraying test
[0085] A field shotcrete application test was conducted in an underground roadway of a coal mine. The shotcrete thickness was 100 mm, and the spraying area was 50 m². The test results are summarized in Table 3.
[0086] Table 3 Performance results of tunnel jetting test in Example 1
[0087]
[0088] Example 2
[0089] This embodiment provides a centimeter-scale coal gangue aggregate roadway shotcrete material and its preparation method. The difference between this embodiment and Embodiment 1 lies in the raw material ratio and some process parameters.
[0090] 1. Raw material ratio
[0091] Coal gangue aggregate: 60% by mass in the shotcrete material. The four-gradation composition is as follows: 0~0.3cm 25%, 0.3~0.6cm 25%, 0.6~0.8cm 25%, and 0.8~1cm 25%.
[0092] Cementitious materials: 40% by mass in the shotcrete material. The mass percentages of each component of the cementitious materials are as follows: 20% ordinary Portland cement (42.5R grade), 50% slag powder (specific surface area 520 m² / kg) (50%), 10% desulfurized gypsum (91% dihydrate gypsum content), 5% silica fume (average particle size 0.15 μm), and 15% secondary fly ash.
[0093] Admixtures: by mass of cementitious materials: 2.0% quick-setting agent (liquid quick-setting agent), 0.4% water-reducing agent (polycarboxylate-based, water reduction rate 35%), and 4% water glass.
[0094] Water-to-binder ratio: 0.40.
[0095] 2. Preparation method
[0096] The preparation method is the same as in Example 1, except that: in step S2, the four-grade ratio is 25%:25%:25%:25%; in step S4, the dry powder mixing time is 6 min; in step S5, the dry mixing time is 5 min; in step S6, the water-cement ratio is 0.40 and the stirring time is 4 min; in step S7, the screw pump pressure is 0.6 MPa, the spraying distance is 1.0 m, the spraying angle is 75°, and the spraying slurry is sprayed within 20 min after mixing.
[0097] 3. Performance Testing
[0098] Performance tests were conducted using the same testing methods as in Example 1. The results of setting time, compressive strength, flexural strength, porosity, permeability coefficient, and tunnel jetting tests are summarized in Table 4.
[0099] Table 4 Summary of Performance Test Results for Example 2
[0100]
[0101] Example 3
[0102] This embodiment provides a centimeter-scale coal gangue aggregate roadway shotcrete material and its preparation method. The difference between this embodiment and Embodiment 1 lies in the raw material ratio and some process parameters.
[0103] 1. Raw material ratio
[0104] Coal gangue aggregate: 70% by mass in shotcrete material. The four-gradation composition is as follows: 0~0.3cm 30%, 0.3~0.6cm 30%, 0.6~0.8cm 20%, and 0.8~1cm 20%.
[0105] Cementitious materials: 30% by mass in the shotcrete material. The mass percentages of each component of the cementitious materials are as follows: 50% ordinary Portland cement (42.5 grade), 24% slag powder (specific surface area 460 m² / kg) (S95 grade), 6% desulfurized gypsum (93% dihydrate gypsum content), 10% silica fume (average particle size 0.25 μm), and 10% grade I fly ash.
[0106] Admixtures: by weight of cementitious materials: 1.0% quick-setting agent (aluminum-oxygen clinker system), 0.2% water-reducing agent (polycarboxylate system, water reduction rate 31%), and 2.5% water glass.
[0107] Water-to-binder ratio: 0.35.
[0108] 2. Preparation method
[0109] The preparation method is the same as in Example 1, except that: in step S2, the four-grade ratio is 30%:30%:20%:20%; in step S4, the dry powder mixing time is 4 min; in step S5, the dry mixing time is 3 min; in step S6, the water-cement ratio is 0.35 and the stirring time is 2.5 min; in step S7, the screw pump pressure is 0.4 MPa, the spraying distance is 1.4 m, the spraying angle is 85°, and the spraying slurry is sprayed within 28 min after mixing.
[0110] 3. Performance Testing
[0111] The performance tests were conducted using the same testing method as in Example 1, and the results are summarized in Table 5.
[0112] Table 5 Summary of performance test results for Example 3
[0113]
[0114] Comparative Example 1
[0115] This comparative example provides a shotcrete material, which differs from Example 1 in that the coal gangue aggregate is not a four-grade mixture, but a single-size coal gangue aggregate (0.3~0.6cm). Other raw material ratios, preparation methods, and testing methods are exactly the same as in Example 1.
[0116] The performance test results are compared with those of Example 1 in Table 6.
[0117] Table 6 Comparison of key performance characteristics between Comparative Example 1 and Example 1
[0118]
[0119] As shown in Table 6, without the four-grade aggregate, the porosity of the shotcrete layer was as high as 26.3%, the rebound rate was as high as 16.8%, and the 28-day compressive strength was only 18.5 MPa. However, after using the four-grade aggregate of the present invention, the porosity decreased to 16.8%, a reduction of 36.1%, the rebound rate decreased to 8.7%, and the strength increased by 56.7%. This indicates that the four-grade aggregate gradation technology of the present invention can effectively reduce the porosity of the shotcrete layer, improve the density and strength of the material, and significantly improve the construction rebound performance.
[0120] Comparative Example 2
[0121] This comparative example provides a sprayed grout material that differs from Example 1 in that it does not contain desulfurized gypsum or silica fume; instead, it uses only ordinary silicate cement and slag powder as the cementing material. The other raw material ratios, preparation methods, and testing methods are exactly the same as in Example 1.
[0122] The performance test results are compared with those of Example 1 in Table 7.
[0123] Table 7 Comparison of key performance characteristics between Comparative Example 2 and Example 1
[0124]
[0125] Compared to Example 1, without the addition of desulfurized gypsum and silica fume, the 28-day compressive strength decreased by 29.9%, the 28-day flexural strength decreased by 30.8%, the porosity increased by 31.5%, and the resilience increased by 66.7%. This indicates that the synergistic combination of desulfurized gypsum and silica fume plays a crucial role in improving the mechanical properties of the shotcrete material, reducing porosity and resilience; neither can be omitted.
[0126] Comparative Example 3
[0127] This comparative example provides a shotcrete material, which differs from Example 1 in that: the mass percentage of coal gangue aggregate in the shotcrete material is 50%, and the mass percentage of cementitious material is 50% (i.e., the amount of coal gangue aggregate is lower than the range of this invention). Other raw material ratios, preparation methods, and testing methods are exactly the same as in Example 1.
[0128] The performance test results are compared with those of Example 1 in Table 8.
[0129] Table 8 Comparison of key performance characteristics between Comparative Example 3 and Example 1
[0130]
[0131] Although increasing the amount of cementitious material improved the 28-day compressive strength (from 28.99 MPa to 25.1 MPa), the actual strength actually decreased. Note the data here: the strength of Comparative Example 3 (25.1 MPa) is lower than that of Example 1 (28.99 MPa), indicating that increasing the amount of cementitious material actually reduced the strength. This may be because the reduced aggregate weakened the skeleton effect. However, the table shows that "Comparative Example 3 decreased by 13.4%", which means that Example 1 was higher. The material cost of Comparative Example 3 increased by 40%. In summary, Comparative Example 3 did not achieve an increase in strength while sacrificing economy and workability; instead, the strength decreased, and the overall benefits were far inferior to those of Example 1.
[0132] Comparative Example 4
[0133] This comparative example provides a shotcrete material, which differs from Example 1 in that the four-stage proportion of coal gangue aggregate is not within the scope of this invention. Specifically, it is 15% for 0~0.3cm, 15% for 0.3~0.6cm, 35% for 0.6~0.8cm, and 35% for 0.8~1cm (the proportion of coarse aggregate is too high). Other raw material proportions, preparation methods, and testing methods are exactly the same as in Example 1.
[0134] The performance test results are compared with those of Example 1 in Table 9.
[0135] Table 9 Comparison of key performance characteristics between Comparative Example 4 and Example 1
[0136]
[0137] Compared with Example 1, after the aggregate gradation ratio deviated from the range of the present invention, the 28-day compressive strength decreased by 25.5%, the porosity increased by 47.0%, and the resilience increased by 81.6%. This indicates that the four gradation ratio ranges defined in the present invention (0~0.3cm accounting for 25%~30%, 0.3~0.6cm accounting for 25%~30%, 0.6~0.8cm accounting for 20%~25%, and 0.8~1cm accounting for 20%~25%) are key technical features that have been optimized and screened. Exceeding this range will seriously affect the various properties of the shotcrete material.
[0138] Comprehensive comparison of various embodiments and comparative examples
[0139] To provide a clear comparison of the overall performance of the various embodiments of the present invention with the comparative examples, the main performance indicators are summarized in Table 10.
[0140] Table 10 Comprehensive Comparison of 28-day Compressive Strength and Key Performance of Each Example and Comparative Example
[0141]
[0142] As can be clearly seen from Table 10, the 28-day compressive strength (27.2~28.99 MPa) of Examples 1 to 3 is significantly higher than that of all comparative examples (18.5~25.1 MPa), while the porosity and resilience are much lower than those of the comparative examples. Particularly noteworthy is that although Comparative Example 3 reduced the coal gangue content (50%) and increased the amount of cementitious material, its strength was actually lower than that of Examples 1 to 3, and its cost increased significantly. This indicates that the present invention achieves excellent comprehensive performance while ensuring a high coal gangue content through gradation and cementitious synergy.
[0143] Industrial Applicability Verification: Permeability Coefficient and Cost-Effectiveness
[0144] To verify the industrial applicability of the technical solution of this invention, a three-month industrial-scale test was conducted underground in a coal mine. The test tunnel was 500m long, with a straight-walled semi-circular arch cross-section, and the shotcrete thickness was 120mm. During the test, approximately 300 tons of the shotcrete material of this invention were used, all prepared from underground coal gangue after crushing and screening.
[0145] The test results show that during the shotcrete construction, the rebound rate of the sprayed material remained stable between 8% and 10%, significantly lower than the 15% to 20% of traditional shotcrete materials; the surface of the shotcrete layer was smooth, with no obvious cracking or peeling; after 28 days of curing, core samples were taken on-site, and the compressive strength was higher than 25 MPa, meeting the roadway support design requirements; compared with traditional shotcrete materials using natural sand and gravel aggregates, each ton of shotcrete material can save about 120 yuan in cost, with a cumulative material cost saving of about 36,000 yuan; during the test, about 195 tons of coal gangue were disposed of, reducing the cost of hoisting and transporting gangue to the surface and the environmental impact.
[0146] Table 11 shows a comparison between the permeability coefficient of the shotcrete material in Example 1 of this invention after 28 days of curing and the requirements of industry standards.
[0147] Table 11 Comparison of Permeability Coefficient (28d) of Example 1 with Industry Standard
[0148]
[0149] As can be seen from Table 11, the permeability coefficient of Example 1 is 0.8 × 10⁻⁶. -11 The speed (m / s) is far below the industry standard requirement (≤5×10). -11 The m / s indicates that the shotcrete material of the present invention has excellent impermeability and can effectively seal the surrounding rock of the tunnel and prevent groundwater from seeping in.
[0150] Table 12 shows a comparison of the overall cost of the centimeter-level coal gangue aggregate roadway shotcrete material of this invention with that of traditional shotcrete materials.
[0151] Table 12 Cost Comparison of the Shotcrete Material of the Present Invention with Traditional Shotcrete Materials (per ton of shotcrete)
[0152]
[0153] As can be clearly seen from Table 12, the overall cost of the shotcrete material of the present invention is reduced by about 30.8% compared with the traditional shotcrete material. This is mainly due to the cost savings in raw materials brought about by replacing natural sand and gravel aggregate with coal gangue aggregate, and replacing part of the cement with slag powder and fly ash.
[0154] Analysis of the principle of this invention: The invention achieves the above-mentioned excellent technical effects, and its principle mainly includes the following aspects:
[0155] Principle of aggregate gradation reconstruction:
[0156] This invention employs a four-graded aggregate system, arranging coal gangue particles with a particle size range of 0-1 cm in a gradient of "fine-medium-relatively coarse-coarse". Specifically, fine particles (0-0.3 cm) fill the voids between particles of 0.3-0.6 cm, particles of 0.3-0.6 cm fill the voids between particles of 0.6-0.8 cm, and particles of 0.6-0.8 cm fill the voids between particles of 0.8-1 cm. This stepwise gradation maximizes the bulk density of the aggregate particles and minimizes the porosity. When the cementitious slurry fills the voids between the aggregate particles, the overall density of the shotcrete material is significantly increased, and the porosity is significantly reduced. Simultaneously, the interlocking of coarse and fine particles in the multi-graded aggregate system forms a stable skeletal structure, which is beneficial for improving the compressive and flexural strength of the shotcrete material.
[0157] Principle of interface-enhanced cementitious system:
[0158] The biggest difference between centimeter-sized coal gangue aggregate and fine aggregate in traditional shotcrete materials lies in the fact that centimeter-sized aggregate has a smaller specific surface area and lower surface energy, resulting in weaker interfacial bonding with the cementitious slurry. This makes it easier for microcracks and pores to form at the interface, leading to a decrease in the mechanical properties and durability of the shotcrete material. This invention solves this technical problem through the synergistic effect of desulfurized gypsum and silica powder.
[0159] The main component of desulfurized gypsum is calcium sulfate dihydrate. During cement hydration, desulfurized gypsum reacts with tricalcium aluminate in cement clinker to form ettringite. Eettringite exists as needle-like crystals and grows at the aggregate-cement interface, filling microcracks and pores. Simultaneously, the formation of ettringite is accompanied by slight volume expansion, which compensates for shrinkage during the hardening process of the cementitious material, reducing shrinkage cracks at the interface.
[0160] Silica powder is an ultrafine dust produced during the industrial smelting of ferrosilicon alloys. With an average particle size of only 0.1–0.3 μm, it possesses extremely high specific surface area and pozzolanic activity. The active SiO2 in the silica powder can react with Ca(OH)2 produced during cement hydration to form CSH gel. CSH gel exhibits a nanoscale flocculent or network structure, capable of filling the nanoscale pores between ettringite crystals and further densifying the interfacial transition zone.
[0161] Electret (micron-sized) and CSH gel (nano-sized) together form a "dual-size gel composite network" at the aggregate-cementing material interface, simultaneously compensating for and strengthening interfacial defects at both the micron and nanoscales. This composite network structure significantly improves the interfacial bonding strength between centimeter-sized coal gangue aggregate and the cementing material, and significantly reduces the porosity of the interfacial transition zone, thus solving the technical problem of high porosity and low strength in the shotcrete layer caused by poor interfacial bonding of centimeter-sized aggregate.
[0162] Synergistic hydration principle of multi-component cementitious materials:
[0163] The cementitious material of this invention comprises five components: ordinary silicate cement, slag powder, desulfurized gypsum, silica fume, and fly ash. These five components promote and synergistically enhance each other during the hydration process.
[0164] The hydration of ordinary silicate cement produces Ca(OH)₂ and CSH gel. Ca(OH)₂ provides an alkaline activation environment for the pozzolanic reaction of slag powder, silica fume, and fly ash. Under the "dual alkali" activation of Ca(OH)₂ and desulfurized gypsum, the glassy structure of slag powder disintegrates, releasing active SiO₂ and Al₂O₃, which participate in the hydration reaction to generate CSH gel and ettringite. Spherical glass microspheres in fly ash also undergo a pozzolanic reaction under alkaline conditions to generate CSH gel, while the "ball effect" of fly ash improves the workability of the sprayed slurry. Ultrafine silica fume particles not only participate in the pozzolanic reaction but also act as physical fillers. Desulfurized gypsum participates in the formation of ettringite and provides a sulfate environment for the activation of slag powder.
[0165] The synergistic hydration of the five components makes the hydration reaction of the cementitious material more complete, the hydration products more abundant, and the microstructure more compact, thus ensuring that the shotcrete material still has excellent mechanical properties and durability under the condition of high coal gangue aggregate content.
[0166] Construction performance optimization principle: In the shotcrete material of this invention, the accelerator accelerates the hydration reaction of the cementitious materials, allowing the shotcrete slurry to quickly solidify and harden after being sprayed onto the tunnel surface, reducing material flow and rebound loss caused by gravity. The water-reducing agent lowers the water-cement ratio of the shotcrete slurry, reducing water consumption while ensuring workability, and improving the density and strength of the shotcrete material. Water glass (sodium silicate) acts as an alkaline activator, activating the pozzolanic activity of slag powder and fly ash. The rational combination of these three admixtures gives the shotcrete material of this invention both good pumping and spraying performance, as well as rapid setting and hardening speed and excellent final mechanical properties.
[0167] The centimeter-scale coal gangue aggregate roadway shotcrete material and its preparation method provided by this invention have broad prospects for industrial application:
[0168] 1. Shotcrete support for underground coal mine roadways. This invention can be directly applied to shotcrete support projects in various types of coal mines, and is particularly suitable for mines with large gangue production. Coal gangue is directly crushed and utilized underground, avoiding the costs and environmental impacts of hoisting and transporting gangue to the surface, and realizing the green mining concept of "gangue not brought to the surface, on-site resource utilization".
[0169] 2. Shotcrete support for other underground engineering projects. The technical solution of this invention is also applicable to shotcrete support for underground engineering projects such as metallurgical mine roadways, water conservancy tunnels, and railway tunnels.
[0170] 3. Resource utilization of industrial solid waste. This invention can dispose of large quantities of industrial solid waste such as coal gangue, slag, desulfurization gypsum, and fly ash, providing a new technical approach for the resource utilization of industrial solid waste.
[0171] 4. Green Mine Construction. This invention aligns with national strategies and the policy direction of green mine construction, and has significant social and environmental benefits.
[0172] In summary, the centimeter-sized coal gangue aggregate roadway shotcrete material and its preparation method provided by this invention, through the synergistic effect of four-grade aggregate gradation reconstruction technology and desulfurized gypsum + silica fume interface-enhanced cementitious system, achieves for the first time a high utilization rate of 60%~70% of 0~1cm centimeter-sized coal gangue aggregate in the shotcrete material. At the same time, it ensures that the shotcrete material has low resilience (≤10%), high strength (28d compressive strength ≥26MPa), low porosity (≤18%) and excellent impermeability. It effectively solves the technical problems of coal gangue accumulation polluting the environment, high cost of traditional shotcrete materials, and low utilization rate of centimeter-sized coal gangue aggregate, and has significant economic, social and environmental benefits, and is worthy of industrial promotion and application.
[0173] The embodiments described herein are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape, and principle of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A centimeter-scale coal gangue aggregate roadway shotcrete material, characterized in that, It consists of the following raw materials by weight percentage: Coal gangue aggregate 60%~70%; Cementitious materials: 30%~40%; And a quick-setting agent comprising 0.8% to 3% of the mass of the cementitious material, a water-reducing agent comprising 0.1% to 0.5% of the mass of the cementitious material, and water glass comprising 2% to 5% of the mass of the cementitious material; The coal gangue aggregate has a particle size of 0-1 cm and is composed of particles of the following four particle size grades according to mass percentage: 0-0.3 cm particles account for 25%-30%, 0.3-0.6 cm particles account for 25%-30%, 0.6-0.8 cm particles account for 20%-25%, and 0.8-1 cm particles account for 20%-25%. The cementitious material is composed of the following components by mass percentage: 20%~50% ordinary Portland cement, 40%~60% slag powder, 6%~10% desulfurized gypsum, 5%~10% silica fume, and 10%~20% fly ash.
2. The centimeter-scale coal gangue aggregate roadway shotcrete material according to claim 1, characterized in that, The ordinary silicate cement is grade 42.5 or grade 42.5R ordinary silicate cement.
3. The centimeter-scale coal gangue aggregate roadway shotcrete material according to claim 1, characterized in that, The slag powder is S95 or S105 grade slag powder with a specific surface area ≥450m² / kg.
4. The centimeter-scale coal gangue aggregate roadway shotcrete material according to claim 1, characterized in that, The desulfurized gypsum contains ≥90% dihydrate gypsum; the average particle size of the silica powder is 0.1~0.3μm; and the fly ash is grade II or higher fly ash.
5. The centimeter-scale coal gangue aggregate roadway shotcrete material according to claim 1, characterized in that, The accelerator is an alumina clinker-based accelerator or a liquid accelerator, with an initial setting time ≤2 min and a final setting time ≤10 min; the water-reducing agent is a polycarboxylate-based high-performance water-reducing agent with a water reduction rate ≥30%.
6. The centimeter-scale coal gangue aggregate roadway shotcrete material according to claim 1, characterized in that, The water-cement ratio of the sprayed material is 0.35~0.
40.
7. A method for preparing a centimeter-scale coal gangue aggregate roadway shotcrete material as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Step S1: Crush the coal gangue raw material to a particle size ≤1cm; Step S2: The crushed coal gangue particles are screened and graded, and collected separately according to four particle size grades: 0~0.3cm, 0.3~0.6cm, 0.6~0.8cm, and 0.8~1cm. They are then mixed evenly in proportions of 25%~30%, 25%~30%, 20%~25%, and 20%~25% by mass to obtain coal gangue aggregate. Step S3: The coal gangue aggregate obtained in step S2 is subjected to magnetic separation to remove iron, and dust suppression spraying is carried out simultaneously during the magnetic separation process. Step S4: Weigh out ordinary Portland cement, slag powder, desulfurized gypsum, silica fume and fly ash according to the proportion, mix them evenly to obtain cementitious material; Step S5: Dry mix the coal gangue aggregate obtained in step S3 with the cementitious material obtained in step S4 for 3-5 minutes to obtain a dry mix. Step S6: Dissolve the quick-setting agent, water-reducing agent and water glass in water to obtain an additive aqueous solution, and then add it to the dry mixture obtained in step S5. Control the water-cement ratio to be 0.35~0.40, stir evenly, and obtain the spray slurry. Step S7: The slurry obtained in step S6 is pumped by a screw pump and sprayed through the spraying equipment.
8. The method for preparing a centimeter-scale coal gangue aggregate roadway shotcrete material according to claim 7, characterized in that, The crushing process described in step S1 uses a combination of jaw crusher and impact crusher, and the maximum particle size of the crushed coal gangue particles does not exceed 1 cm.
9. The method for preparing a centimeter-scale coal gangue aggregate roadway shotcrete material according to claim 7, characterized in that, In step S3, the magnetic separation for iron removal uses a permanent magnet separator or an electromagnetic separator with a magnetic field strength ≥3000Gs; the dust suppression spraying uses an atomized spraying method with a spraying water volume of 1%~3% of the coal gangue aggregate mass.
10. The method for preparing a centimeter-scale coal gangue aggregate roadway shotcrete material according to claim 7, characterized in that, The spraying construction described in step S7 adopts either wet spraying or damp spraying; in the wet spraying method, the spraying slurry is sprayed within 30 minutes after mixing; the pumping pressure of the screw pump is 0.3~0.8MPa, the spraying distance is 0.8~1.5m, and the spraying angle is 70°~90°.
Citation Information
Patent Citations
Coal gangue roadway spraying material and preparation method thereof
CN115321888A
Material for spraying lower tunnel of supporting well and its preparation method
CN1281829A